Patterns of variability in the 2017 super-Eddington outburst of Swift J0243.6+6124 - Cassity, A.; Bailyn, C.; Vasilopoulos, G. (American Astronomical Society Meeting Abstracts #235, 2020)
Swift J0243.6+6124 is a Be/X-ray binary and the first known ultraluminous X-ray pulsar in our Galaxy that reached a peak luminosity Lx > 1039 erg s-1 during its 2017-2018 outburst. The proximity of this system allows for the study of super-Eddington accretion as an analog of distant ultraluminous X-ray sources. We used data from the Neil Gehrels Swift X-ray Telescope to investigate the evolution of the spectral and temporal properties of this system, looking for characteristic transitions that could reveal changes in the accretion regime with Lx. A first transition is found in the hardness-intensity diagram at Lx ~ 7 x 1036 erg s-1. The system exhibits a harder-when-brighter trend that changes to a softer-when-brighter trend. This transition is typical in Galactic BeXRB pulsars, and is often used as a proxy of the magnetic field strength of the neutron star. A second transition is indicated by changes in fractional variability and spectral hardness at a critical luminosity Lcrit ~ 3 x 1038 erg s-1. Pulsations exhibit single peak behavior and change to double peak following the transition. Associating these transitions with the formation and evolution of the accretion column can help us derive constraints on the magnetic field of the neutron star, and gain insights on super-Eddington accretion.